InstantScope: a low-cost whole slide imaging system with instant focal plane detection - Guo, Kaikai (Biomed Opt Express, 2015)
We report the development of a high-throughput whole slide imaging (WSI) system by adapting a cost-effective optomechanical add-on kit to existing microscopes. Inspired by the phase detection concept in professional photography, we attached two pinhole-modulated cameras at the eyepiece ports for instant focal plane detection. By adjusting the positions of the pinholes, we can effectively change the view angle for the sample, and as such, we can use the translation shift of the two pinhole-modulated images to identify the optimal focal position. By using a small pinhole size, the focal-plane-detection range is on the order of millimeter, orders of magnitude longer than the objective’s depth of field. We also show that, by analyzing the phase correlation of the pinhole-modulated images, we can determine whether the sample contains one thin section, folded sections, or multiple layers separated by certain distances – an important piece of information prior to a detailed z scan. In order to achieve system automation, we deployed a low-cost programmable robotic arm to perform sample loading and $14 stepper motors to drive the microscope stage to perform x-y scanning. Using a 20X objective lens, we can acquire a 2 gigapixel image with 14 mm by 8 mm field of view in 90 seconds. The reported platform may find applications in biomedical research, telemedicine, and digital pathology. It may also provide new insights for the development of high-content screening instruments.